ANALISIS MANAJEMEN PELAKSANAAN PROGRAM PROMOSI KESEHATAN DALAM PROGRAM PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) TATANAN RUMAH TANGGA DI UPTD PUSKESMAS DTP BANDAR TAHUN 2023 - Dewi, Mustika; Batubara, Saiful (Jurnal Penelitian Kesmasy, 2024)
Public Health Center is the main health care model that plays a to achieve the Sustainable Development Goals (SDGs), through Clean and Healthy Behavior in Indonesia. It is a promotion and prevention measure society to promote healthy lifestyles among people. This qualitative study describes Clean and healthy behavior program implemented at UPTD DTP Bandar. Depth interviews were conducted between 5 (five) informants consisting of the Head of the Health Resources and Community Empowerment Division at the Health Service, the Head of the UPTD DTP Bandar, responsible person Health Promotion, the village midwife and cadres at the UPTD DTP Bandar. The results of the study showed that there were systemic problems In the program of clean and healthy behavior Program which caused reduction in coverage compared to previous years. Two of the the most important is smoked behavior in home with breastfeeding between mothers. Also in the main role the Clean and Healthy Behavior Program is for cadres who are only trained once a year in October. In addition, that must also interact with community leaders to support programs in their area. Adding information, facilitating with advocating through coordination between the Board of Health, Community Health Centers, community to solve the problems managers and health cadres are needed. In addition, occupational health promotion officers are is also required carry out promotional and proactively actions that runs smoothly in the community.